Biosimilars : design and analysis of follow-on biologics - Chow, Shein-Chung. (Boca Raton : CRC Press, 2014)
"This is the first book entirely devoted to the design and analysis for assessment of biosimilarity and drug interchangeability of biosimilars, and test for comparability in manufacturing processes of biologic products. It covers all of the statistical issues that may occur in biosimilar studies under various study designs at various stages of research and development of biologic products"--
"Biologic drug products are therapeutic moieties that are manufactured using a living system or organism. These are important life-saving drug products for patients with unmet medical needs. They also comprise a growing segment in the pharmaceutical industry. In 2007, for instance, worldwide sales of biological products reached $94 billion US dollars, accounting for about 15% of the pharmaceutical industry's gross revenue. Meanwhile, many biological products face losing their patents in the next decade"--
Includes bibliographical references (pages 397-410) and index.
Keywords: Pharmaceutical biotechnology; Pharmaceutical biotechnology industry; Drugs -- Generic substitution; Pharmaceutical policy; Biological products; MATHEMATICS / Probability & Statistics / General; MEDICAL / Pharmacology